Self-preserving dispositions and strategies of modern Russian youth - Peresypkin, Larisa V. Verzunova, Inna S. Shapovalova, Oleg N. Polukhin, Anastasiya V. Kisilenko, Andrey P. (Opción, 2019)
The paper covers the results of a Russian study on the determination of self-preserving dispositions and strategies of modern Russian youth via comparative qualitative research methods. As a result of the study, the problem field of control over the self-preserving behaviour of young people was determined, at the perimeter of which there are problems related to the lack of work to prevent diseases among young people, uncontrolled smoking and the use of alcohol by young people. In conclusion, self-realization can be transformed through children as well.